The Effect of Adding Turmeric Powder (Curcuma domestica Val.) and Patin Fish (Pangasius sp.) on the Physical, Chemical, and Preference Level of Fish Balls - Albab, Miftakhu Ulil; Pujimulyani, Dwiyati; Fitri, Ichlasia Ainul (Fakultas Pertanian Universitas Veteran Bangun Nusantara, 2025)
Turmeric is a spice that contains curcuminoid compounds with various benefits for body health. Meatballs are a food that is loved by the community and is generally made from beef. Beef has high levels of cholesterol and saturated fatty acids. The use of catfish has the advantage of being cheaper and lower in cholesterol and the addition of turmeric is expected to produce meatballs that have antioxidant activity. The purpose of that study was to determine the effect of the addition of turmeric powder and catfish meat variations on antioxidant activity and fish balls preference. A 2-factorial Complete Random Design (RAL) was used with the addition of turmeric powder (1; 1.5; and 2 g) and a variety of catfish meat (50; 75; and 100 g). Fish meatballs were evaluated physically (color and texture), level of preference (color, texture, taste, aroma, and overall), as well as chemical analysis on the selected meatballs (moisture content, ash content, protein content, fat content, antioxidant activity of the DPPH method, total phenols, and flavonoids). The results showed that the combination of 2 g turmeric powder and 100 g catfish meat resulted in selected fish balls based on preference tests. The results of the analysis of selected meatballs showed a moisture content of 66.09% b/b, ash 5.9% b/b, protein 38.62% b/b, fat 8.77% b/b, antioxidant activity of 28.20% RSA, total phenol 4.96 mg EAG/g db, and flavonoid content of 0.58 mg EK/g db . Fish balls with varying proportions of catfish meat and the addition of turmeric powder significantly affected the physical properties (color and texture) and had a notable impact on the acceptability and chemical properties of the catfish fish balls. Keywords: meatballs, catfish, turmeric, antioxidant activity, preference test